Effect of sex steroid hormones on the number of serotonergic neurons in rat dorsal raphe nucleus. (6th May 2015) - Kunimura, Yuyu; Iwata, Kinuyo; Iijima, Norio; Kobayashi, Makito; Ozawa, Hitoshi
Highlights: In adult rat brain, sex steroid hormones do not affect serotonin neuron number. These hormones do not affect tryptophan hydroxylase-immunoreactive cell number. Serotonin-immunoreactive signal intensity in dorsal raphe is sexually dimorphic. This subregion-specific sexual dimorphism is independent of sex hormone levels. Abstract: Disorders caused by the malfunction of the serotonergic system in the central nervous system show sex-specific prevalence. Many studies have reported a relationship between sex steroid hormones and the brain serotonergic system; however, the interaction between sex steroid hormones and the number of brain neurons expressing serotonin has not yet been elucidated. In the present study, we determined whether sex steroid hormones altered the number of serotonergic neurons in the dorsal raphe nucleus (DR) of adult rat brains. Animals were divided into five groups: ovariectomized (OVX), OVX + low estradiol (E2), OVX + high E2, castrated males, and intact males. Antibodies against 5-hydroxytryptamine (5-HT, serotonin) and tryptophan hydroxylase (Tph), an enzyme for 5-HT synthesis, were used as markers of 5-HT neurons, and the number of 5-HT-immunoreactive (ir) or Tph-ir cells was counted. We detected no significant differences in the number of 5-HT-ir or Tph-ir cells in the DR among the five groups. By contrast, the intensity of 5-HT-ir showed significant sex differences in specific subregions of the DR independent of sex steroid levels, suggesting that the manipulation of sex steroid hormones after maturation does not affect the number and intensive immunostaining of serotonergic neurons in rat brain. Our results suggest that, the sexual dimorphism observed in the serotonergic system is due to factors such as 5-HT synthesis, transportation, and degradation but not to the number of serotonergic neurons.